The Influence of Work Engagement on Turnover Intention Mediated by Job Satisfaction of Bakti Timah Medika Nurses - Muchtadin; Zelvy Emmelya Sundary (International Journal of Applied Research and Sustainable Sciences, 2023)
This research is aimed at finding out the magnitude of the influence of work engagement on turnover intention, mediated by job satisfaction. Respondents were 82 Bakti Timah Medika nurses selected through convenience sampling. The research design is quantitative with a data analysis method in the form of SEM-PLS. The research results found that work engagement had no direct effect on turnover intention. Work engagement will have a negative effect on turnover intention if it is mediated by job satisfaction. Job satisfaction fully mediates the negative influence of work engagement on turnover intention. Future research can use work stress as mediator variables. This research contributes to nursing practice regarding turnover intention through increasing job satisfaction and work engagement.